2015
DOI: 10.1002/chem.201501223
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Globular Precursors

Abstract: o-Carborane (C2 B10 H12 ) was adapted to perform as the core of globular macromolecules, dendrons or dendrimers. To meet this objective, precisely defined substitution patterns of terminal olefin groups on the carborane framework were subjected to Heck cross-coupling reactions or hydroboration leading to hydroxyl terminated arms. These led to new terminal groups (chloro, bromo, and tosyl leaving groups, organic acid, and azide) that permitted ester production, click chemistry, and oxonium ring opening to be pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Table 3 shows a downfield shift (∆δ = +10.1 ppm) of the B(9,10) resonances of 9,10-(allyl) 2 -1,7-closo-C 2 B 10 H 10 (3) vs the corresponding B(9,10)-H ones in the parent m-carborane. A similar downfield (∆δ = +10.6 ppm) is reported for the B(9,12) vertexes of 9,12-(allyl) 2 -1,2-closo-C 2 B 10 H 10 with respect to the B(9,12)-H vertexes of the parent o-carborane [14]. The 11 B{ 1 H} NMR spectrum provides information on the electron density surrounding B atoms in the cluster vertexes, so it can be concluded that the effect of a B-allyl vertex concerning to the former B-H in the 11 B{ 1 H} NMR of both isomers is almost the same, ∆δ +10.6 ppm and +10.1 ppm, for oand m-, respectively.…”
Section: Characterization Of Di-branched M-carborane Derivatives At Tsupporting
confidence: 77%
See 4 more Smart Citations
“…Table 3 shows a downfield shift (∆δ = +10.1 ppm) of the B(9,10) resonances of 9,10-(allyl) 2 -1,7-closo-C 2 B 10 H 10 (3) vs the corresponding B(9,10)-H ones in the parent m-carborane. A similar downfield (∆δ = +10.6 ppm) is reported for the B(9,12) vertexes of 9,12-(allyl) 2 -1,2-closo-C 2 B 10 H 10 with respect to the B(9,12)-H vertexes of the parent o-carborane [14]. The 11 B{ 1 H} NMR spectrum provides information on the electron density surrounding B atoms in the cluster vertexes, so it can be concluded that the effect of a B-allyl vertex concerning to the former B-H in the 11 B{ 1 H} NMR of both isomers is almost the same, ∆δ +10.6 ppm and +10.1 ppm, for oand m-, respectively.…”
Section: Characterization Of Di-branched M-carborane Derivatives At Tsupporting
confidence: 77%
“…Therefore, di-branched m -carborane derivatives ( Scheme 2 ) with precise patterns of substitution are prepared by judicious choice of the synthetic procedure using similar conditions to the preparation of o -carborane derivatives present in previous work [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations